Industrialización de granos andinos “elaboración de pan integral de quínoa (Chenopodium Quínoa Willd) y amaranto (Amaranthus Caudatus. L) - Jeréz Garcés, Darwin Ernesto (2017)
At present, the development of bread has a good development, which motivates to look for new ways of combining raw materials for its industrialization, thus developing new production alternatives to improve the nutritional level. Reasons for the present investigation, the objective of which was "TO PRODUCE INTEGRAL BREAD OF QUINOA (Chenopodium Quinoa Willd) AND AMARANTO (Amaranthus Caudatus L.) Using a suitable technological process in order to acquire a good quality product. After the final product was obtained the physical-chemical and microbiological analysis of the best treatment was carried out and the following results were obtained: 2.37% ash, 9.10% protein, 30.6% humidity, 10.9% Fat 6,79% total dietary fiber, 40,2% total carbohydrates, 1236 KJ / 100g energy, 295 kcal / 100g energy, 246,3 cm3 volume, molds <10 CFU / g, yeasts <10 CFU / g, coliforms < 10 CFU / g, Staphilococcus aureus <10 CFU / g and salmonella <10 CFU / g the same ones that were made in the Laboratory of Food Control and Analysis "LACONAL", being established within the parameters required by The INEN standards 2945 (Annexed 21) After having performed the physical-chemical analysis, the resulting product was compared with a market product (Grile y Supan) 4% protein while quinuamarant integral bread has 9%, was averaged Calculate the cost of the processed product, giving a total of 1, 29 USD per 54 g, while the market has a cost of 1.15 USD per 54 g, so it is concluded that enriched bread has a higher protein content, being favorable for consumption and marketing.